An interactive method for multi-criteria dispatching problems with unknown preference functions. (June 2020) - Chou, Ywh-Leh; Lin, Te-Yu; Wu, Jei-Zheng; Wu, Cheng-Hung
Highlights: An interactive centroid method (ICM) is developed for multi-objective dispatching problems. The ICM method considers unknown nonlinear preference functions of decision makers. Indecisive thresholds are adopted to model the bounded rationality of decision makers. Numerical results show the superiority in solution quality and computational time using empirical manufacturing data. The method enhances the efficiency of human-computer interaction in a smart factory of Industry 3.5. Abstract: This research investigates multi-criteria dispatching problems with unknown user preference functions to help decision makers (DMs) find solutions that meet their multi-criteria preferences. The explicit consideration of the following factors distinguish this research from previous literature: (1) dispatching management with three conflicting objectives, (2) nonlinear preference functions with unknown weights, (3) indecisive threshold that models the bounded rationality of DMs, and (4) near optimal solution through a small number of interactions. In a smart factory of Industry 3.5, the proposed interactive centroid method (ICM) enhances the efficiency of human–computer interaction and improves the quality of multi-criteria manufacturing decisions significantly. Our extensive numerical study reveals that the ICM algorithm finds near optimal solutions under linear or quadratic utility functions through less than a dozen interactions with DMs. The average gap between the ICM solutions and true optimal is merely 1.537% and 0.882% under quadratic and linear utility functions, respectively.